Can thousand rivers reduce its poverty using its rivers? Can "thousand rivers" reduce its poverty using its rivers? - Vadra, Jorghi; Sihaloho, Estro Dariatno (FORUM EKONOMI, 2019)
West Kalimantan is one of the Provinces in Kalimantan island known as Thousand Rivers province because it has many rivers, either small or big rivers, including Kapuas river, the longest river in Indonesia. According to Statistical Bureau (BPS), West Kalimantan has the poorest people among other provinces in Kalimantan with 405,510 people living in poverty and becomes the poorest province in Kalimantan with Rp337, 228 per capita per month. This paper uses panel data to analyze regression model of regencies and cities in West Kalimantan from 2011 until 2015. Authors find effects from geographical aspect to regional poverty, especially gross regional product depending on river, such as transportation and logistics, plantation, and forestry this model also sees the effects of unemployment on regional poverty. Authors use number of poor people, in this case we call Poverty as dependent variable, and Gross Regional Product in River, Gross Regional Product in Plantation, Gross Regional Product in Forestry, and Unemployment Rate in each regencies and cities as output. The result shows gross regional product in river has significant effects into poverty. It also shows negative relationship between gross regional products in river into poverty. Increases 1 million rupiahs of Gross Regional Product in River, Poverty will decrease 0.15%. However, increases 1 million rupiahs of Gross Regional Product in Plantation, Poverty will increase 0.02% , increases 1 million rupiahs of Gross Regional Product in Forestry, Poverty will increase 0.03% , increases 1 million rupiahs of Gross Regional Product in Mining and Quarrying, Poverty will increase 0.04%. Unemployment rate also has positive relationship with poverty, as long as decreases 1% of total unemployment, poverty will decrease about 0.28%.